Pengaruh Budaya Organisasi, Komunikasi Interpersonal, dan Perilaku Inovatif, terhadap Motivasi Kerja Guru Sekolah Dasar Negeri di Kabupaten Labuhan Batu - Siregar, Marlina; Wow, Yasaratodo; Hambali, Hambali (Universitas Negeri Malang, 2023)
Abstract: The purpose of this research is to determine and analysis: (1) the effect of organizational culture on innovative behavior, (2) the effect of interpersonal communication on innovative behavior, (3) the effect of organizational culture on work motivation, (4) the effect of interpersonal communication on work motivation, and (5) the effect of innovative behavior on work motivation. The research subjects were the teachers of the State Elementary School of Labuhan Batu Regency with a total sample of 142 people taken by means of stratified proportional random sampling, the data were analyzed using path analysis after calculating the correlation of all research variables in the form of a matrix.. The analysis results of the effect exogenous variables on endogenous variables in each substructure obtained (1) organizational culture, interpersonal communication, and innovative behavior have a positive effect on teacher work motivation by 7.7%; 4.7% and 9.7% (2) innovative behavior is influenced by teacher work motivation by 5.3%. The results of the study illustrate that (1) there is a direct positive influence of organizational culture on innovative behavior by 5.24%, (2) there is a direct positive influence of interpersonal communication on innovative behavior of 3.09%, (3) there is a direct positive influence of organizational culture on work motivation, (4) there is an effect of interpersonal communication on work motivation, and (5) there is an influence of innovative behavior on work motivation.. Keyword: Organizational Culture, Interpersonal Communication, Innovative Behavior, and Work Motivation Abstrak: Tujuan penelitian ini adalah untuk mengetahui dan menganalisis: (1) pengaruh budaya organisasi terhadap perilaku inovatif, (2) pengaruh komunikasi interpersonal terhadap perilaku inovatif, (3) pengaruh budaya organisasi terhadap motivasi kerja, (4) pengaruh komunikasi interpersonal terhadap motivasi kerja, dan (5) pengaruh perilaku inovatif terhadap motivasi kerja. Subjek penelitian adalah para guru Sekolah Dasar Negeri Kabupaten Labuhan Batu dengan jumlah sampel sebanyak 283 orang yang diambil dengan cara stratified proportional random sampling, data dianalisis dengan menggunakan analisis jalur setelah dihitung korelasi seluruh variabel penelitian dalam bentuk matriks. Hasil analisis pengaruh variabel eksogen terhadap variabel endogen pada masing-masing substruktur diperoleh (1) budaya organisasi, komunikasi interpersonal, dan perilaku inovatif berpengaruh positif terhadap motivasi kerja guru sebesar 7,7%; 4,7% dan 9,7% (2) perilaku inovatif dipengaruhi oleh motivasi kerja guru sebesar 5,3%. Hasil penelitian memberikan gambaran bahwa (1) ada pengaruh langsung positif budaya organisasi terhadap perilaku inovatif sebesar 5,24%, (2) ada pengaruh langsung positif komunikasi interpersonal terhadap perilaku inovatif 3,09%, (3) ada pengaruh langsung positif budaya organisasi terhadap motivasi kerja, (4) ada pengaruh komunikasi interpersonal terhadap motivasi kerja, dan (5) ada pengaruh perilaku inovatif terhadap motivasi kerja. Kata Kunci: Budaya Organisasi, Komunikasi Interpersonal, Perilaku Inovatif, dan Motivasi Kerja